1982
DOI: 10.1111/j.1540-6261.1982.tb02223.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of the Federal Reserve's Margin Requirement

Abstract: A portfolio-theoretic model of the optimal margin account is developed. It is argued that the Federal Reserve's goal in setting the margin requirement is to influence investor equity ratios. Using the average equity ratio as the dependent variable and the arguments of the model as independent variables, an empirical model is estimated. It is concluded that the margin requirement is an effective regulatory tool. THE STATE OF THE art with respect to the question of the effectiveness of theFederal Reserve's initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Largay does report that price volatility decreased after the imposition of 100 percent margins, but the empirical results are not givenY The direct effectiveness of the Fed's margin requirements on reducing borrowing (in broker margin accounts) was presented by Luckett (1982). Luckett does find evidence that increased margin requirements reduced borrowing in the 1966--1979 period; his empirical estimates indicate "... that a 10 percent change in the Federal Reserve's margin requirement will change investor equities on stocks held in margin accounts at security dealers by about 1 1/2 to 2 percent" (p. 794).…”
Section: Empirical Literature On Margin Requirementsmentioning
confidence: 99%
“…Largay does report that price volatility decreased after the imposition of 100 percent margins, but the empirical results are not givenY The direct effectiveness of the Fed's margin requirements on reducing borrowing (in broker margin accounts) was presented by Luckett (1982). Luckett does find evidence that increased margin requirements reduced borrowing in the 1966--1979 period; his empirical estimates indicate "... that a 10 percent change in the Federal Reserve's margin requirement will change investor equities on stocks held in margin accounts at security dealers by about 1 1/2 to 2 percent" (p. 794).…”
Section: Empirical Literature On Margin Requirementsmentioning
confidence: 99%
“…Aside from margin requirements, households' decisions to borrow more on margin are also expected to be positively related to the past real stock market index (here the S&P 500) 3 , and negatively related to risk and to the consumer credit burden. Following earlier work, risk is measured as the difference between the yields on Moody's Baa-and Aaa-rated bonds (Luckett 1982). Finally, the effects of real income and households wealth are ambiguous.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Grube et al (1979) found that lower margin requirements are linked to higher aggregate prices, but that there was no correlation between higher margin requirements and prices. Further, Luckett (1982) examined the impact of margin requirements on equity holdings and found that margin requirements are an effective regulatory tool as higher margin requirements reduce equity holdings.…”
Section: Introductionmentioning
confidence: 99%
“…We can point to only two books [Geelan and Rittereiser, 1998;Curley, 2008], three papers [Rudd and Schroeder, 1982;Fiterman and Timkovsky, 2001;Coffman et al, 2010b] devoted to margining algorithms and two papers [Fortune, 2000[Fortune, , 2003 devoted to margining practice. Literature on studying the influence of margin requirements on the market, such as for example [Moore, 1966;Luckett, 1982], is more representative; see the related survey in [Kupiec, 1998]. The vast majority of publications on margining consists primarily of regulatory circulares and manuals written by security market lawyers.…”
Section: Introductionmentioning
confidence: 99%